Problem-solving leaning on new thinking skills - Eisner, Howard, 1935- (CRC Press, 2021)
Problem-solving and better thinking skills are among the top skills that employers are looking for. This book presents various methods of problem-solving that can be adapted to any field. It focuses on a set of a dozen new approaches with an ending result to finding better solutions to problems that you may have previously found difficult. The book discusses problem-solving based upon new thinking skills and presents the relationship between problem-solving and creativity. A connection between problem-solving and re-engineering is presented as the book explores the ability to tackle new and difficult problems in all aspects of life. It points you in the direction of how to easily find better solutions to problems that previously were found to be difficult. Target audience is general engineers, systems engineers, scientists, technologists, mathematicians, and lawyers.